Keputusan Pembelian dan Kepuasan Konsumen Jeruk Lokal Rimau Gerga Lebong di Pulau Sumatera (Jurnal Agribisnis Indonesia, 2024)
Rimau gerga lebong orange (hereafter referred to as gerga orange) is a local orange variety of Bengkulu Province which is currently developed as a national superior commodity. It is important to understand the consumer behaviour to developing this local orange. The purpose of this study is to analyze the purchasing decision process and consumer satisfaction with gerga orange. This study uses primary data from an online survey of 200 respondents taken deliberately in Bengkulu, South Sumatra, and Jambi provinces in April and May 2022. Data were analyzed using descriptive methods, customer satisfaction index (CSI), and importance-performance analysis (IPA). In CSI and IPA analyses, this study uses eight attributes of oranges: taste, juicyness, freshness, colour, size, price, promotion, and product availability. The results of the purchase decision showed that most consumers buy gerga oranges because the benefits of vitamin C that contain in gerga oranges, obtain information from previous purchasing experiences, consider taste attributes in the pre-purchase evaluation, decide to buy gerga oranges due to situational factors, and express satisfaction and are willing to repurchase gerga oranges. Based on CSI analysis, the results showed that the level of consumer satisfied with the purchase and consumption of gerga oranges. Based on IPA analysis, the attribute of gerga lebong rimau oranges that needed improvement was fruit availability. The results of this study can provide benefits to breeders or fruit growers in developing varieties of gerga oranges according to consumer needs and preferences and for marketers to develop marketing strategies for gerga oranges more precisely.